Treatment of vertigo in elderly patients with chronic cerebrovascular disease - S. N. Duma (Неврология, нейропсихиатрия, психосоматика)
Dizziness can be caused by different problems in elderly patients; the possibilities of drug therapy are limited; betahistine dihydrochloride is most commonly used.Objective: to investigate the efficiency and safety of combination therapy with mexidol and betahistine in patients with vertigo according to the global assessment scale for treatment efficiency.Patients and methods. The investigation enrolled 89 elderly patients (mean age, 73.7 years) with chronic cerebrovascular disease and complaints of dizziness. Neurological, otoneurological (the orthostatic test, the forced hyperventilation test, the Dix–Hallpike test, the Tinetti test, and the visual vertigo analogue scale), somatic, cognitive and emotional statuses were evaluated in all the patients. The patients were randomized into two groups. A study group included patients who took betahistine 48 mg/day, intravenous Mexidol® 5.0 ml for 10 days, then 375 mg tablets daily for 50 days; a comparison group consisted of patients who used only betahistine 48 mg/day for 60 days. The efficiency of treatment in both groups was evaluated using the global scale on day 60 of therapy, by taking into account the opinion of a physician and a patient.Results. In the elderly patients, vertigo was caused by several problems in the majority (75%) of cases. The combined (betahistine + mexidol) treatment group showed a more significant (more than double) reduction in the symptoms of vertigo than the comparison group.Conclusion. In elderly patients with chronic cerebrovascular disease and vertigo, combined therapy with betahistine and mexidol, which has neuroprotective properties, improves the results of treatment.